Formulasi Sediaan Sabun Mandi Cair dari Jus Lidah Buaya (Aloe barbadensis Mill.) - Kartiningsih Kartiningsih; Deni Rahmat (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Aloe vera leaf contains hydroxyanthraquinone derivatives, aloin (barbaloin and the distereoismeric 10-C glucosides of aloe-emodin anthracene) and 7-hydroxyaloin isomer and to a lesser extent aloe emodin, chrysophanol, chromone derivative and aloeresin as major glycoside-anthracene derivative. The aloin content varies in different species of aloe. The main constituent of aloin is barbaloin which is a pale yellow crystalline glycoside, soluble in water. Recent studies confirm that aloe has an antibacterial (against Staphylococcus ssp. and Streptococcus ssp.) and a fungicidal activity, so it can be used as antiseptic agent. The main purpose of this research was to obtain a physically stable liquid soap containing aloe vera. The formulation contained sodium lauryl ether sulphate with various concentrations. The obtained liquid bath soaps were evaluated cencernng their stability i.e.: viscosity, surface tension, and pH for eight weeks. Each formula gave a viscosity in the range of 8100 to 10400 cps and showed a pseudoplastic flow.